2018
DOI: 10.1088/1361-6528/aaa2dd
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and optical response optimization of Ge/Si quantum dots transformed from the sputtering-grown Ge thin film by manipulating the thermal annealing

Abstract: A series of zero-dimensional Ge/Si quantum dots (QDs) samples are fabricated by inducing the transformation from the two-dimensional Ge thin film, which is grown by the traditional direct current (DC) magnetron sputtering, via regulating the annealing process. The QD density increases sharply after the post rapid thermal annealing (PRTA). The observations of atomic force microscopy (AFM) and Raman spectroscopy suggest that the good morphology of Ge QDs results from an appropriate thermodynamics and kinetics su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…As Figure 5 shows, the Raman spectra of samples M 550 , M 650 , and M 750 , a strong characteristic peak stem from Ge-Ge transverse optical vibration was observed at around 300 cm −1 in each sample. The symmetrical shape and low FWHM (full width at half maximum) of the Ge-Ge peak indicated that the deposited Ge layers have good crystallinity, which was consistent with our previous work [15] in which Ge has a high crystallization while the growth temperature > 550 • C. The broad peak near 400 cm −1 shown in each sample was caused by the vibration of the Ge-Si intermixed atoms, the increase of the peak intensity and the decrease of the peak width as the growth temperature rose from 550 • C to 750 • C meant the Ge-Si intermixing intensified with the accelerated diffusion of atoms, which confirmed the inference from Figures 3 and 4 that the growth and evolution of QDs in samples M 550 , M 650 , and M 750 was accompanied by the process of mutual mixing of atoms.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As Figure 5 shows, the Raman spectra of samples M 550 , M 650 , and M 750 , a strong characteristic peak stem from Ge-Ge transverse optical vibration was observed at around 300 cm −1 in each sample. The symmetrical shape and low FWHM (full width at half maximum) of the Ge-Ge peak indicated that the deposited Ge layers have good crystallinity, which was consistent with our previous work [15] in which Ge has a high crystallization while the growth temperature > 550 • C. The broad peak near 400 cm −1 shown in each sample was caused by the vibration of the Ge-Si intermixed atoms, the increase of the peak intensity and the decrease of the peak width as the growth temperature rose from 550 • C to 750 • C meant the Ge-Si intermixing intensified with the accelerated diffusion of atoms, which confirmed the inference from Figures 3 and 4 that the growth and evolution of QDs in samples M 550 , M 650 , and M 750 was accompanied by the process of mutual mixing of atoms.…”
Section: Resultssupporting
confidence: 91%
“…In recent years, fruitful research [11][12][13][14] of fabricating QDs by magnetron sputtering have negated the preexisting preconception that the high kinetic energy of particles and the high deposition rate of magnetron ion beam sputtering might induce drastic growth that leads to the formation of polycrystalline islands and the inhibition of the formation of self assembled QDs. Magnetron sputtering is gradually developing into an emerging QD growth technique even though its relevant literatures are still few, and the corresponding obtained evolution mechanism of QDs are still focused on the single-layer structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These evolutions agreed with that of their counterparts grown by MBE [10]. Furthermore, similar density-decrease and sizeincrease behaviors found in the pure Ge QDs, which experienced the post-annealing process, were attributed to the diffusion of Ge adatom and the Ostwald ripening growth of Ge islands [26,27]. It suggested that the bonding amount of Mn-Ge during the initial stage of nucleation formation can enhance the diffusion of Ge adatom and favor ripening growth.…”
Section: Resultssupporting
confidence: 79%